Plasma carotenoids and medial temporal lobe atrophy in older adults. Issue 4 (April 2021) - Thomas, Aline; Proust-Lima, Cécile; Baillet, Marion; Helmer, Catherine; Delcourt, Cécile; Foubert-Samier, Alexandra; Catheline, Gwénaëlle; Féart, Catherine; Samieri, Cécilia
Summary: Background & aims: Carotenoids are vegetable pigments with neuroprotective properties. Clinical studies found efficacy of specific carotenoids on improving brain perfusion and functioning with aging. However, evidence of an effect on neurodegeneration, which may require longer follow-up period to observe, is more limited. Leveraging biomarkers from a large population-based cohort study of older adults, we investigated whether blood carotenoids were associated with atrophy of the medial temporal lobe (a biomarker of neurodegeneration in aging) over 10 years. Methods: This study included 461 dementia-free participants from the Three-City Bordeaux study (aged ≥65) who had plasma carotenoids measured at baseline and up to three repeated brain imaging exams in the subsequent 10 years. Results: In adjusted linear mixed models, each increase of 1 SD in plasma level of total carotenoids and of β-carotene was associated with 0.02 cm 3 (95% CI, 0.001–0.04; P  = 0.04) and 0.02 cm 3 (95% CI, 0.01–0.04; P  = 0.008) smaller medial temporal lobe volume loss per year, respectively. Conclusions: Our results based on a unique long-term prospective evaluation of a neuroimaging biomarker suggest a beneficial role of carotenoids for the prevention of age-related neurodegeneration.